2021
DOI: 10.17221/129/2021-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural market information in developing countries: A literature review

Abstract: In most developing countries, the agricultural industry has the potential to alleviate poverty at a faster rate compared to other sectors. As such, many governments have initiated policies and programme to improve agricultural performance. However, some of these projects have not achieved success because the local agricultural markets are often controlled by a small group of stakeholders who tend to hide information in the market despite having huge market power. This paper aimed to determine the issues and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
0
7
0
1
Order By: Relevance
“…Smallholders can use mobile phones to access information on technologies and good practices when access to formal education institutions and printing materials is limited [10]. Mobile phones can promote farmers' trading [11], allowing farmers and other parties in remote areas to communicate more easily [12].…”
Section: The Role Of Mobile Phone Usage In Smallholder Farmingmentioning
confidence: 99%
“…Smallholders can use mobile phones to access information on technologies and good practices when access to formal education institutions and printing materials is limited [10]. Mobile phones can promote farmers' trading [11], allowing farmers and other parties in remote areas to communicate more easily [12].…”
Section: The Role Of Mobile Phone Usage In Smallholder Farmingmentioning
confidence: 99%
“…Developing countries that are dominated by people with lower middle income have the potential to develop export concentrations, sectors and markets (Osakwe et al, 2018). Governments in developing countries have begun to initiate policies and programs in the context of accelerating economic growth through the agricultural sector (Nugroho, 2021).…”
Section: Theoritical Underpinningmentioning
confidence: 99%
“…To derive maximum benefits, smallholder farmers need to be knowledgeable about mobile phone use when accessing agricultural marketing information. Studies (Bruns et al , 2022; Kumaravel et al , 2022; Nugroho, 2021; Rahman et al , 2020; Raza et al , 2020) revealed that smallholder farmers used mobile phones to access agricultural marketing information. On the contrary, Dewi et al (2021) and Folitse et al (2018) indicated that farmers relied more on friends, family, neighbors, personal experience and cooperative societies in accessing agricultural marketing information.…”
Section: Introductionmentioning
confidence: 99%